Efficient Charge Transfer and Effective Active Sites in Lead‐Free Halide Double Perovskite S‐Scheme Heterojunctions for Photocatalytic H2 Evolution. Issue 3 (15th January 2023) - Lv, Huijun; Yin, Hongfei; Jiao, Na; Yuan, Chunyu; Weng, Suting; Zhou, Kailing; Dang, Yangyang; Wang, Xuefeng; Lu, Zhen; Zhang, Yongzheng
Abstract: The practical application of lead‐free double perovskite Cs2 AgBiBr6 in photocatalytic H2 evolution is still restricted due to the low activity and poor stability. The rational design of lead‐free halide double perovskites heterojunctions with efficient charge transfer and effective active sites is a potential route to achieve the ideal prospect. Herein, in this work an S‐scheme heterojunction of Cs2 AgBiBr6 with enriched Br‐vacancies and WO3 nanorods (VBr ‐Cs2 AgBiBr6 /WO3 ) obtaining excellent visible‐light responsive photocatalytic H2 evolution performance and durable stability is reported. The S‐scheme heterojunction driven by the unaligned Fermi levels of these two semiconductors ensures the efficient charge transfer at the interface, and density functional theory calculations reveal the enriched Br vacancies on Cs2 AgBiBr6 (022) surfaces introduced by atom thermal vibration provide effective active sites for hydrogen evolution. The optimized VBr ‐Cs2 AgBiBr6 /WO3 S‐scheme photocatalyst exhibits the photocatalytic hydrogen evolution rate of 364.89 µmol g −1 h −1 which is 4.9‐fold of bare VBr ‐Cs2 AgBiBr6 (74.44 µmol g −1 h −1 ) and presents long‐term stability of 12 h continuous photocatalytic reaction. This work provides deep insights into the photocatalytic mechanism of VBr ‐Cs2 AgBiBr6 /WO3 S‐scheme heterojunctions, which emerges a new strategy in the applications of perovskite‐based photocatalysts. Abstract : A rod‐on‐octahedron S‐scheme heterojunction by VBr ‐Cs2 AgBiBr6 and WO3 is rationally constructed. Enriched Br vacancies on Cs2 AgBiBr6 (022) surfaces are introduced by atom thermal vibration during solvothermal process, which are the effective active sites for hydrogen evolution. The as‐prepared S‐scheme heterojunction exhibits a superior photocatalytic performance over the other perovskite‐based catalysts, emerging a new strategy in the applications of perovskite‐based photocatalysts.